Progressive Freeze Concentration of Coconut Water (Jurnal Teknologi (Sciences & Engineering), 2014)
In order to provide convenience for consumers around the world, it is highly beneficial if the nutritious coconut water (CW) could be concentrated and just easily be added with water for later consumption. A new concentration technique is required to eliminate some parts of the water from the CW while retaining its nutritious and unique aroma. As Progressive Freeze Concentration (PFC) could retain the nutritional compounds, it was applied to concentrate CW and reduce its volume. In PFC system, only a single block of ice is formed as a layer on the cooled surface. A coil stainless steel crystallizer was used as FC unit to investigate the enhancement of sugar content in CW. The effect of initial concentration of CW was then investigated on the performance of the PFC system through the Effective Partition Constant (K) value and increment of sugar content. It was found that low initial concentration and intermediate coolant temperature yielded lower K value and high increment of sugar content. The best K achieved was 0.3101 and the highest increment of sugar content was 53% at initial concentration of 3 %Brix and coolant temperature of 12Â°C.